Pengenalan Perbanyakan Bibit Tanaman Buah Pada Masyarakat - Novalina, Lusi; Fariadi, Herri (LPPM Universitas Dehasen Bengkulu, 2024)
The 2023 Dehasen University Bengkulu Community Service Program (KKN) was held at the Department of Food Crops Horticulture and Plantations UPTD BITPHPP in Tabalagan Village, Semidang Lagan District, Central Bengkulu Regency, Bengkulu Province. The work program carried out during this KKN period is